The Influence Practice: The Case of Cámara del Comercio y la Producción de Concepción Between 1957 and 1971 and Its Network [el Ejercicio de la Influencia: El Caso de la Cámara del Comercio y la Producción de Concepción Entre 1957 y 1971 y Sus Redes] - Moyano-Barahona, C; Rivas-Rodriguez, J (Universidad Austral de Chile, 2014)
The main focus of this analysis is the historical forms through which the social elites exert their power and influence in local areas. The organization analyzed is the Chamber of Production and Commerce of the southern city of Concepción between the years 1957 and 1971; the main focus is on the Chamber s social and political strategies which made possible its influence and actions in the defence of the main economic and entrepreneurial interests of its members. At a time of decisive changes in the role of the State in the economy, of intense debates about the country s economic and social development this article analyzes the ways and means through which local entrepreneurs, themselves part of the local elite, displayed their actions in the regional realm in order to preserve their own condition as elite.